Aspects of Performance Practice in Bologna in the Sixteenth and Seventeenth Centuries: a Study of Archival Sources (2016)
At the end of 16th century, Bologna was one of themost influential cities of the Papal States and culturallyone of the main centres in Italy where a network ofpolitical and artistic forces connected the activities ofcivic and church institutions. The Concerto Palatino ofthe Signoria of Bologna took part in liturgical and paraliturgicalevents that included musical instruments inthe vocal ensemble where the various combinations ofvoices and instruments offered new sonic solutions thatinfluenced the development of local musical repertoires.The civic church of San Petronio was one of the maincentres of musical innovation of the city and its archivalsources allow for a reconstruction of local performancepractice at the beginning of the seventeenth century.